Unes consideracions sobre la dietarística valenciana del segle XVII - Escartí, Vicent Josep (Caplletra. Revista Internacional de Filologia, 2015)
In this paper a series of considerations are developed about Valencian diarists of the xvii century, some generic and textual constants are extracted from them and the significance of this documentary corpus for linguistic history is evaluated.